2022
DOI: 10.3390/ijerph19063446
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Profile of Elite Polish Short Track Athletes: An Analysis of Temperamental Traits and Impulsiveness

Abstract: The aim of this study was to determine the temperament and impulsiveness profile of short track athletes. Professional athletes (juniors and seniors), under training in the Polish National Team (Nfemale = 21, Nmale = 19, Mage = 20), completed The Temperament and Character Inventory- Revised (TCI-R (56)) and a shortened version of the Urgency, Premeditation, Perseverance, Sensation-Seeking, Positive Urgency, Impulsive Behavior Scale (S-UPPS-P). The results proved that skaters obtain higher scores than the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
4
1
Order By: Relevance
“…Competitive women athletes self-reported greater positive urgency impulsivity which was in contrast to pre-pandemic studies reporting no gender difference ( Holfelder et al, 2020 ; Gabrys and Wontorczyk, 2022 ). However, gender differences in urgency have been reviewed as unlikely to moderate the likelihood of maladaptive outcomes ( Cyders, 2013 ; DeVito et al, 2020 ), which was also confirmed by our lack of gender by urgency interactions.…”
Section: Discussioncontrasting
confidence: 88%
“…Competitive women athletes self-reported greater positive urgency impulsivity which was in contrast to pre-pandemic studies reporting no gender difference ( Holfelder et al, 2020 ; Gabrys and Wontorczyk, 2022 ). However, gender differences in urgency have been reviewed as unlikely to moderate the likelihood of maladaptive outcomes ( Cyders, 2013 ; DeVito et al, 2020 ), which was also confirmed by our lack of gender by urgency interactions.…”
Section: Discussioncontrasting
confidence: 88%
“…This study contributes significantly to the theoretical analysis of impulsive behavior in athletes, making several noteworthy contributions. Firstly, prior research on athlete impulsivity has predominantly focused on aspects such as competitive anxiety ( Terres-Barcala et al, 2022 ) and psychological characteristics ( Gabrys and Wontorczyk, 2022 ). However, there has been limited exploration into the specific nature of athlete impulsive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity is typically characterized by a lack of careful consideration and an inability to resist immediate temptations ( Gabrys and Wontorczyk, 2022 ). On the other hand, self-reflection promotes a deeper understanding of one’s actions, decisions, and motivations ( González-Hernández et al, 2019 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is described in terms of the process involved: motor (i.e., action without thought), perceptual–attentional (i.e., lack of concentration on the task), and lack of planning or transcendence (i.e., prioritising when, how, and where the action occurs without giving value to the consequences for the future) [ 8 , 9 , 10 ]. In sport contexts, impulsive responding has been related both to the pursuit of greater and faster efforts to be perfect [ 11 ], fear of failure [ 12 ], and even self-destruction [ 13 ], and to negative emotions such as anger, aggressive behaviours, concentration difficulties, and poor performance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%